Comparison of Local Infiltration Versus Superficial Cervical Plexus Block for Central Venous Catheter Insertion in Awake Adult Patients - Khan, Zafarullah; khan, Abid; Niaz, Faisal; Iqbal, Salman; Doltani, Deepak Rai; Qadri, Anjum Anwar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To measure the frequency of pain and satisfaction (Linkert score) with two local anesthesia techniques for central venous line insertion in awake patients. Study Design: Quasi-Experimental Study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, Pakistan from Jul to Dec 2023. Methodology: After seeking approval from the Ethical Committee, a sample of 170 patients was randomized into two Groups. One Group was given subcutaneous local infiltration, and the other was given a superficial cervical plexus block before central venous catheter insertion. Results: There were 40(47.1%) patients in Group LWI who felt mild pain, 42(49.4%) patients who felt moderate pain, and 3(3.5%) patients who felt severe pain. 41(48.2%) patients were satisfied in Group LWI and 44(51.8%) patients were not satisfied with the intervention. In Group, CPB, 71(83.5%) patients experienced mild pain, and 13(15.3%) patients experienced moderate pain. None of the patients felt severe pain, with a value of less than 0.001. Seventy-two (84.7%) patients in Group CPB were satisfied, while only 13(15.3%) conveyed dissatisfaction on the basis of linkert score. Conclusion: We concluded that the superficial cervical plexus block provided superior analgesia for central venous catheter placement in awake patients with better patient satisfaction.